Hubungan Paritas Dengan Kejadian Rupture Perineum Di Rs Daerah Kabupaten Manufahi Timor Leste - Barros, Alexandrina; Wahyuni, Candra (Journal of Health Science Community, 2021)
Perineal rupture is experienced by 85% of women who have vaginal delivery. Perineal rupture needs attention because it can cause dysfunction of the female reproductive organs, as a source of bleeding, and a source, or a way in and out of infection, which can then cause death due to bleeding or sepsis (Chapman, 2006; Manuaba, 2008). Based on a preliminary study at the District Hospital of Manufahi, East Timor in 2020, data on pregnant women in October 2019 were 10 people, and there were still many primigravida mothers who suffered perineal tears. This research is a cross sectional study. The population in the study were all maternity mothers who came to the Regional Hospital of Manufahi Regency East Timor in 2020, amounting to 44 respondents. The independent variable in this study is parity with an ordinal scale and the dependent variable is perineal rupture with an ordinal scale. This research instrument uses a standardized questionnaire and observation sheet. The analysis of this study uses the Spearman rank test. In the analysis of the Spearman test p-value = 0.002 <α = 0.05 (p-value <α) which means that H0 is rejected and H1 is accepted, which means that there is a relationship between parity and perineal rupture. So mothers with primiparous status have a higher risk for experiencing severe perineal rupture events. This is due to the effects of mothers who experience fear when undergoing the first labor, edema during labor and delivery with the help of tools